Aristotelian Roots of Contemporary Tense Logic - Živilė PABIJUTAITĖ; Pranciškus GRICIUS (Studia Universitatis Babeș-Bolyai. Philosophia, 2024)
Tense logic is a branch of contemporary logic which includes formal devices that allow us to deal with the temporal relations between propositions. The aim of our paper is threefold: 1) to reveal how Aristotelian philosophical ideas about time, truth, possibility and necessity were reinterpreted by the founder of contemporay tense logic Arthur Prior; 2) to discuss what novel solutions to the classical problem of future contingents are available using Priorean invention; 3) to describe how the tools of tense logic have transcended their original theoretical purposes.